2012
DOI: 10.1128/aem.06466-11
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic and Physiological Characterization of the Verrucomicrobia Isolate Diplosphaera colitermitum gen. nov., sp. nov., Reveals Microaerophily and Nitrogen Fixation Genes

Abstract: Previously we reported the cultivation of novel verrucomicrobia, including strain TAV2 (93% 16S rRNA gene identity to its nearest cultivated representative, Opitutus terreae PB90-1) from the gut of the termite Reticulitermes flavipes. To gain better insight into the Verrucomicrobia as a whole and understand the role of verrucomicrobia within the termite gut ecosystem, we analyzed a draft genome and undertook a physiological characterization of TAV2. Strain TAV2 is an autochthonous member of the R. flavipes gut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
84
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(91 citation statements)
references
References 80 publications
4
84
0
3
Order By: Relevance
“…Our proteomic results indicated the presence of specific peptides corresponding to the dinitrogenase reductase (NifH) only when cells were grown with 2% O 2 , corroborating our previous findings for the presence of nitrogen fixation genes (nif) and growth on N-free medium (Wertz et al, 2012). Finally, the expression of a urea-binding signal peptide protein and the a-subunit of urease may indicate a role for TAV2 in the recycling of uric acid excreted by the host.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Our proteomic results indicated the presence of specific peptides corresponding to the dinitrogenase reductase (NifH) only when cells were grown with 2% O 2 , corroborating our previous findings for the presence of nitrogen fixation genes (nif) and growth on N-free medium (Wertz et al, 2012). Finally, the expression of a urea-binding signal peptide protein and the a-subunit of urease may indicate a role for TAV2 in the recycling of uric acid excreted by the host.…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study confirm the microaerophilic nature of strain TAV2 (Wertz et al, 2012), with a higher growth rate observed for cells grown under 2% O 2 than those grown under 20% O 2 . The long lag-phase shown for cells grown in 20% O 2 suggests the need of an acclimation period and the possibility of cells being under oxidative stress.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations